2008
DOI: 10.1074/jbc.m709848200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Ligase Smurf1 Mediates Tumor Necrosis Factor-induced Systemic Bone Loss by Promoting Proteasomal Degradation of Bone Morphogenetic Signaling Proteins

Abstract: Chronic inflammatory disorders, such as rheumatoid arthritis, are often accompanied by systemic bone loss, which is thought to occur through inflammatory cytokine-mediated stimulation of osteoclast resorption and inhibition of osteoblast function. However, the mechanisms involved in osteoblast inhibition remain poorly understood. Here we test the hypothesis that increased Smad ubiquitin regulatory factor 1 (Smurf1)-mediated degradation of the bone morphogenetic protein pathway signaling proteins mediates reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(140 citation statements)
references
References 39 publications
(39 reference statements)
12
127
0
1
Order By: Relevance
“…We have previously demonstrated that one mechanism by which TNF· suppresses osteoblast differentiation is through NF-κB-mediated antagonism of TGFß-and BMP-2-induced SMAD signaling in differentiating osteoblasts (17). These data are consistent with the demonstration that NF-κB signaling up-regulates SMAD7, an inhibitor of SMAD activation in osteoblastic cells (18) and that TNF· promotes systemic bone loss by promoting proteasomal degradation of bone morphogenetic signaling proteins through up-regulation of SMAD ubiquitination regulatory factor 1 (Smurf1) (19). Recently, a direct inhibitory action of NF-κB on bone formation has been ratified in vivo where time-and stage-specific inhibition of the inhibitor of κB kinase (IKK) in differentiated osteoblasts increased trabecular bone mass and bone mineral density (BMD) and ameliorated ovariectomy-induced bone loss by promoting a compensatory increase in bone formation (20).…”
Section: Introductionsupporting
confidence: 77%
“…We have previously demonstrated that one mechanism by which TNF· suppresses osteoblast differentiation is through NF-κB-mediated antagonism of TGFß-and BMP-2-induced SMAD signaling in differentiating osteoblasts (17). These data are consistent with the demonstration that NF-κB signaling up-regulates SMAD7, an inhibitor of SMAD activation in osteoblastic cells (18) and that TNF· promotes systemic bone loss by promoting proteasomal degradation of bone morphogenetic signaling proteins through up-regulation of SMAD ubiquitination regulatory factor 1 (Smurf1) (19). Recently, a direct inhibitory action of NF-κB on bone formation has been ratified in vivo where time-and stage-specific inhibition of the inhibitor of κB kinase (IKK) in differentiated osteoblasts increased trabecular bone mass and bone mineral density (BMD) and ameliorated ovariectomy-induced bone loss by promoting a compensatory increase in bone formation (20).…”
Section: Introductionsupporting
confidence: 77%
“…TNF␣ suppresses BMP2-induced osteoblast differentiation and increases the expression of Smurf1, leading to the subsequent degradation of Smad1 and Runx2, which are critical mediators of BMP2 signaling (25,43). Smurf1 interacts directly with Smad1 and Runx2, and stimulates the degradation of these proteins in ubiquitin-and proteasome-dependent manners (44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence that TNF␣ suppresses RUNX2 and osterix as well as bone morphogenetic protein-induced osteoblast differentiation (2,(67)(68)(69). Hence, these alternative mechanisms may contribute to the attenuating effects of Dex and TNF␣ on osteoblastogenesis.…”
Section: Discussionmentioning
confidence: 99%